Avaliação do desempenho dos métodos de proteção contra a perda de excitação em geradores síncronos: uma contribuição utilizando a teoria dos conjuntos nebulosos - Morais, Adriano Peres de (2008)
This work aims to evaluate the performance of the loss of field protection methods in synchronous generators. The methods are introduced to make available in a single text the various ways to protect the synchronous generator against the loss of field. The conventional methods have some problems, and the main of them is the improper operation caused by the power stable oscillations. In order to solve or minimize the relay algorithm malfunction, two new methods of loss of field protection are proposed. The first is designed to increase the operational area of the generator on steady state conditions, bounded by the conventional loss of field protection. It was accomplished by modifying the operational characteristic of the mho relay, which is better coordinated with the generator capability curve. The second makes use of loss of field conception in a fuzzy set theory. With the objective to identify the performance of each one, the methods were evaluated through computational simulations of loss of field and stable power oscillation. The methods were set and evaluated according to the generator parameters (Xd and X'd). Since, tests in three machines with different parameters were carried out. So it was possible to conclude that the methods do not behave the same way for different generators parameters. On the other hand, the proposed technique, which is based on the fuzzy set theory was more efficient and not have been affected by the generator parameters and system considered.